The Relationship Between Sleep Patterns and Academic Performance: A Cross-Sectional Study Among Nursing Students in Bayero University, Kano - Rajah, Amina Suleiman; Olatunde, Solomon Ayomide; Bello, Umar Lawal; Garko, Muhammad Ali; Dalhatu, Adamu; Bashir, Sadisu; Usman, Usman Muhammad; Shehu, Bello Sani; Haruna, Jonah Japhet; Aliyu, Fatima Musa (Journal of Practical Nurse Education and Practice)

(untitled) (NorQuest College, 2026)
This study aimed to (1) assess the sleep patterns (duration and quality) of nursing students, (2) examine the relationship between sleep duration and academic performance (CGPA), and (3) explore factors contributing to poor sleep patterns among nursing students. Sleep patterns significantly influence academic performance, especially in demanding fields like nursing. However, there is limited research on the relationship between sleep quality, sleep duration, and academic performance among nursing students. A cross-sectional descriptive design was used. Data were collected through self-administered questionnaires given to 166 nursing students in Bayero University, Kano. Pearson and Spearman correlations were conducted to assess relationships between sleep variables and academic performance. The majority of students reported inadequate sleep duration and irregular sleep schedules. The Pearson correlation between sleep duration and CGPA was weak and not statistically significant (r =0.088, p = 0.261). Similarly, the Spearman correlation between sleep quality and CGPA was also weak and not significant (ρ = 0.036, p = 0.646). Factors such as academic workload, stress, and screen time were the primary contributors to poor sleep quality. The findings suggest that although nursing students at Bayero University face significant sleep challenges, there is no significant association between sleep patterns and academic performance. Interventions to improve sleep hygiene may benefit students’ well-being and academic success.